2021
DOI: 10.1016/j.yebeh.2020.107675
|View full text |Cite
|
Sign up to set email alerts
|

LoVE in a time of CoVID: Clinician and patient experience using telemedicine for chronic epilepsy management

Abstract: As part of our ongoing interest in patient-and family-centered care in epilepsy, we began, before the onset of the CoVID-19 pandemic, to evaluate the concerns and preferences of those delivering and receiving care via telemedicine. CoVID-19 arrived and acted as an unexpected experiment in nature, catalyzing telemedicine's widespread implementation across many disciplines of medicine. The arrival of CoVID-19 in Ireland gave us the opportunity to record these perceptions pre-and post-CoVID. Data were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
3
26
0
2
Order By: Relevance
“…Logically speaking, the review of concept and theoretical notions should take place prior to the measurement of this construct, while the analysed papers studied patient satisfaction in the reverse order. There were also papers in which satisfaction was not defined at all [43,[46][47][48][49]53,56,61,[64][65][66][67]72,80]. Taking into account both the survey questionnaires developed by the authors as well as well-defined, known, validated and reliable measures, these treat satisfaction as a multi-dimensional construct.…”
Section: Recommendations For Preparing Research On Patient Satisfaction With Remote Healthcarementioning
confidence: 99%
“…Logically speaking, the review of concept and theoretical notions should take place prior to the measurement of this construct, while the analysed papers studied patient satisfaction in the reverse order. There were also papers in which satisfaction was not defined at all [43,[46][47][48][49]53,56,61,[64][65][66][67]72,80]. Taking into account both the survey questionnaires developed by the authors as well as well-defined, known, validated and reliable measures, these treat satisfaction as a multi-dimensional construct.…”
Section: Recommendations For Preparing Research On Patient Satisfaction With Remote Healthcarementioning
confidence: 99%
“…Telemedicine has been a key feature of health systems' response to ensuring people can access care in a safe manner during Covid-19. In many countries, including Ireland, telemedicine is a key form of accessing primary and hospital care (Banks et al, 2021;Greenhalgh et al, 2020;Homeniuk and Collins, 2021). In some systems, telemedicine technology has been linked to EHR systems to allow the monitoring of patients through a continuum of services (Ford et al, 2020).…”
Section: Covid-19 Patient Carementioning
confidence: 99%
“…Figure 4.3 presents the key findings from an analysis which examined increased use of telemedicine for outpatient department (OPD) care for people with epilepsy (Banks et al, 2021 Banks et al (2021) also found that the vast majority of clinicians who undertook the OPD consultations felt that the patient was appropriate for a virtual encounter (~90%), and they were happy that the patient could continue their routine care virtually (~75%) (Banks et al, 2021). In addition, the authors found that a majority of patients with epilepsy were happy to have their care provided virtually if their condition remained stable.…”
Section: Telemedicine In Hospital Carementioning
confidence: 99%
“…2,3 While studies indicate that both persons with epilepsy (PWE) and epilepsy specialists are content with remote consultations, additional research is needed to determine its main benefits for the diagnostic and treatment process. [3][4][5] We investigated factors that will be relevant for a seamless transition to a post-pandemic world and may represent innovations of the patient-specialist interaction in epilepsy care.We report a nationwide cross-sectional online survey with focus on epilepsy care among members of the Lithuanian Association of Neurology. The aims of our study were to outline the experience of neurology specialists when providing services for PWE during the global COVID-19 pandemic, determine neurologists' views on vaccination against COVID-19 and telehealth.…”
mentioning
confidence: 99%
“…2,3 While studies indicate that both persons with epilepsy (PWE) and epilepsy specialists are content with remote consultations, additional research is needed to determine its main benefits for the diagnostic and treatment process. [3][4][5] We investigated factors that will be relevant for a seamless transition to a post-pandemic world and may represent innovations of the patient-specialist interaction in epilepsy care.…”
mentioning
confidence: 99%